ENVIRONMENTAL PROBLEMS IN CITIES OF MADHYA PRADESH: मध्य प्रदेश के नगरों मे पर्यावरणीय समस्यायंे - kesharwani, Savita (International Journal of Research -GRANTHAALAYAH, 2015)
Geographically Madhya Pradesh is the second largest state in India with a total population of 7 crore 25 lakhs and the urban population is 20069806. The urbanization ratio in Madhya Pradesh is 27.63%. Which is less than the national ratio. But in terms of total urban population, many states of India are more than the total population. Presently, Madhya Pradesh is administratively divided into 242 tehsils and 313 development blocks in 51 districts. There are municipal corporations in 14 districts of the state and the total number of towns is 476. The population of 4 metros in Madhya Pradesh is more than 10 lakh and there are 28 cities whose total population is between 1 lakh and 10 lakh. It should be known that the proportion of total urban population of cities with more than 1 lakh population in the state is more than 60%. But due to lack of planned and strategic development in the state, many types of environmental problems have arisen as a result of which the pace of economic, social, and cultural development in the cities has slowed down. भौगोलिक दृष्टि से मध्य प्रदेश भारत का दूसरा सबसे बड़ा राज्य है जिसकी कुल जनसंख्या 7 करोड़ 25 लाख है तथा नगरीय जनसंख्या 20069806 है मध्य प्रदेश मे नगरीकरण अनुपात 27.63ः है। जो राष्ट्रीय अनुपात से कम है। परंतु कुल नगरीय जनसंख्या की दृष्टि से भारत के कई राज्यों की कुल जनसंख्या से भी ज्यादा है। वर्तमान मे मध्य प्रदेश मे प्रशासनिक रूप से 51 जिलों मे कुल 242 तहसील तथा 313 विकासखण्डों मे विभक्त है। राज्य के 14 जिलों मे नगर निगम है तथा कुल नगरो की संख्या 476 है। मध्य प्रदेश मे 4 महानगरों की जनसंख्या 10 लाख से ज्यादा है तथा 28 नगर ऐसे हैं जिनकी कुल जनसंख्या 1 लाख से 10 लाख के बीच है। ज्ञातव्य हो की राज्य मे 1 लाख से ज्यादा जनसंख्या वाले नगरों की कुल नगरीय जनसंख्या का अनुपात 60ः से ज्यादा है। परंतु राज्य मे नियोजित और रणनीतिक विकास के आभाव मे कई प्रकार की पर्यावरणीय समस्याएं सामने आई हैं जिसके परिणाम स्वरूप नगरों मे आर्थिक, सामाजिक, और सास्कृतिक विकास की गति धीमी पड़ी है।